Strengthening Mawar Melati Women Farmers Group Capacity to Improve Family Economic Resilience in Oo Parese Village - Nurul Mufida; Mardiyah; Milda; Irka; jalil, Abdul (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2026)
This community empowerment program implemented by PT. Hannah Asa Indonesia focused on strengthening the entrepreneurial and financial management capacities of the Mawar Melati Women Farmers Group (KWT) in Oo Parese Village, Sigi Regency. Prior to the program, group members lacked a systematic approach to financial recording and cost management in their business operations. Through the training, participants learned to calculate Cost of Goods Sold (COGS), determine appropriate selling prices, and maintain accurate daily financial records. They also developed marketing and presentation skills, including the preparation of business profiles and pitch decks. The program employed a combination of interactive workshops, mentoring, and practice-based learning. As a result, participants became more confident in presenting their businesses to potential investors and partners. The findings demonstrate that continuous capacity building and mentoring effectively enhance women’s entrepreneurial roles, contributing to improved family welfare and local economic resilience.